Experimental Design for Acid Content Determination in Organic Acid - Kumaraguru A/L Gunasegaran, Kumaraguru (Universiti Teknologi Petronas, 2009)
My research is on acid content determination in the organic acid. The primary objective of the project is to design and develop the experimental procedures to determine the acid content of organic acid. Before proceeding with the experimental design, I will utilize the existing methods of determining the acidity of organic acid. The already available methods are using the pH probe and also performing the Total Acid Number (TAN) measurement. For the TAN measurement, specifically the Potentiometric Titration will be utilized to evaluate the acid content of the acid sample. The second main task will be the identification of the indirect measurement parameters of the organic acid. This is to correlate those parameters' values with the acidity of the organic acid. The main experiment, which is Potentiometric Titration by using the auto-titrator, already been conducted. Several runs of experiments were preformed and the results were analyzed in order to achieve the primary objective of this project. The other indirect measurement parameters, were identified upon thorough research on the properties of the organic acid (acetic acid) and the relevant experiments were conducted sequentially, after the Potentiometric Titration experiment